Short-Term Continuous Positive Air Pressure Treatment: Effects on Quality of Life and Sleep in Patients with Obstructive Sleep Apnea - Kondratavičienė, Laima; Malakauskas, Kęstutis; Vaitukaitienė, Guoda; Balsevičius, Tomas; Žemaitis, Marius; Miliauskas, Skaidrius (Medicina (Kaunas, Lithuania), 2022)
Background and Objectives: The aim of this study was to evaluate short-term continuous positive air pressure (CPAP) treatment for health-related quality of life (HRQL) in patients with obstructive sleep apnea. Materials and Methods: Our subjects were 18–65 years old, diagnosed with moderate-to-severe obstructive sleep apnea and treated with CPAP between January 2020 and June 2021 in Hospital of Lithuanian University of Health Sciences Kaunas clinics. All the patients completed the Epworth Sleepiness Scale (ESS), the 36-Item Short Form Health Survey (SF-36), the and Pittsburgh Sleep Quality Index (PSQI) before and after 3 months of treatment. Polysomnography was also repeated. Statistical analyses were performed using SPSS 27.0 software. The value of p < 0.05 was considered as statistically significant. Results: The active-treatment group comprised 17 subjects with a mean age of 51.9 ± 8.9 years. The total SF-36 questionnaire score improved from 499.8 ± 122.3 to 589.6 ± 124.7 (p = 0.012). The SF-36 role limitations due to emotional problems (p = 0.021), energy (fatigue) (p = 0.035), and general health (p = 0.042) domains score significantly improved after CPAP treatment for 3 months. The PSQI mean score at baseline was 12.6 ± 2.9 and in the post-treatment group, it was −5.5 ± 2.3 (p = 0.001). The ESS also changed significantly from a pretreatment mean score of 10.9 ± 5.7 to −5.3 ± 3.2 (p = 0.002) after 3 months. Conclusions: Improvement in HRQL is seen even after a short treatment period with CPAP. Questionnaires are a good tool to evaluate CPAP treatment efficacy.